RELATIONSHIP BETWEEN FINANCIAL INCLUSION AND ECONOMIC GROWTH: RELATIONSHIP BETWEEN EVIDENCE FROM ARDL MODELLING - Ibrahim Musa; Sule Magaji; Ali Salisu; Achi O Peter (Indonesian Journal Of Business And Economics, 2022)
ABSTRACTThis study examines the impact of financial inclusion on economic growth in Nigeria from 1986 to 2020. The Zivot-Andrew unit root test was used to examine the statistical characteristics of the data. The Zivot Andrew unit root test shows that while Automated Teller Machines and foreign direct investment are stationary at level, the gross domestic product, commercial bank branches, and phone-based transactions are stationary at first difference. Bound test for long run shows that there is long run relationship among the variables of interest. According to the Auto Regressive Distributive Lag (ARDL) result, commercial bank branches in Nigeria have a short-term, positive, and significant impact on the country's gross domestic product. The Nigerian gross domestic product is negatively impacted by automated teller machines; however, this impact is negligible. The long run coefficient demonstrates positive and statistically significant influence of commercial bank branches on Nigeria's GDP. The Nigerian gross domestic product has positively and statistically significantly impacted by automated teller machines. Mobile phone-based transaction has positive and significant impact on gross domestic product in Nigeria. In Nigeria, foreign direct investment has a positive and statistically significant impact on GDP. Both in terms of sign and size, the error correction term (ECT) satisfies all theoretical and statistical requirements. The ECT coefficient is -0.522626 with a 5% level of significance. This shows that at 52.26 percent, the disequilibrium brought on by the shock in the years before is corrected to the long-term equilibrium in the present year. The Granger causality test demonstrates that while mobile phone-based transactions do not granger cause gross domestic product, commercial bank branches, automated teller machines, domestic depositors' money in banks, and foreign direct investment do. The studies recommend, the Central Bank of Nigeria should push commercial banks to increase the number of automated teller machines in each branch.Keywords: Financial inclusions, FDI, Economic growth ARDLJEL: P43.